“Inheriting” our Cultural Heritage Changes of Paradigm of Conservation - Musso, Stefano Francesco (ICONARCH International Congress of Architecture and Planning, 2014)
The world is quickly and deeply changing, facing new challenges in the built environment. Conservation can play a crucial role for preserving the future of the planet, not wasting but rather continuing to use (or reuse) the depot of physical traces that the previous ages left us, as provisional responsible for them, in cultural ways and respectful. A crucial question rises apropos: are we really ready and able to inherit this impressive mine of knowledge, identity and cultural richness? We cannot in fact go on along the paths that have been traced, within the western world and culture, since more than two centuries about conservation/restoration (with all its contradictions and suggestions). We cannot behave as if nothing has changed and ignoring the problems of the contemporary societies, or like they were external to our commitments, interests and responsibilities. The key-lecture will deal with some of the main challenges that the culture of conservation (or movement, as someone could call it) will have to face in the near future in order to survive and not to reduce itself to an ancillary role and to an un-influencing condition within the contemporary world. A particular focus will be put for this reason on the crucial role that ICT play also in this field.